2016
DOI: 10.1007/s40090-016-0109-5
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and desorption kinetics of toxic organic and inorganic ions using an indigenous biomass: Terminalia ivorensis seed waste

Abstract: Environmental remediation has been a strategy employed by scientists to combat water pollution problems that have led to the scarcity of potable water. Hence, in this study, Terminalia ivorensis seed waste (TISW) was explored for the removal of Congo Red, Methylene Blue, Cadmium and Lead from aqueous solutions. Some experimental variables such as pH, biosorbent dose, initial solute ion concentration, agitation time and temperature were optimised. The surface microstructures of TISW were studied using proximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 61 publications
0
6
0
1
Order By: Relevance
“…[1,2] Cellulose and lignin could bind with heavy metals, which are dependent on their source of origin and relevant fraction of various constituents. [3][4][5] Similarly, a group of researchers reported that hemicellulose and pectin also could bind heavy metals (Pb, Cu, and Cd) that can improve health via fiber-containing food. [6] Various researchers investigated dietary fiber in terms of its potential to scavenge heavy metals after it enters the body [7][8][9] and to elucidate the dietic factors that could affect the heavy metal-binding capacity, some endogenous factors like proteins and exogenous factors like pH.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Cellulose and lignin could bind with heavy metals, which are dependent on their source of origin and relevant fraction of various constituents. [3][4][5] Similarly, a group of researchers reported that hemicellulose and pectin also could bind heavy metals (Pb, Cu, and Cd) that can improve health via fiber-containing food. [6] Various researchers investigated dietary fiber in terms of its potential to scavenge heavy metals after it enters the body [7][8][9] and to elucidate the dietic factors that could affect the heavy metal-binding capacity, some endogenous factors like proteins and exogenous factors like pH.…”
Section: Introductionmentioning
confidence: 99%
“…First is the diffusion of adsorbate (PSMMs) through the solution to the external surface of the adsorbent (AFZ) or the boundary layer diffusion of the adsorbate or solute molecules (surface or boundary layer diffusion); second is the gradual adsorption, in which intraparticle diffusion may be a rate-limiting step (intraparticle diffusion); third is the diffusion of adsorbate particles to adsorption sites either by pore diffusion through the liquid-filled pores or by a solid diffusion mechanism (pore diffusion or solid diffusion). Some of the adsorbates are adsorbed onto the adsorbent by a combination of one, two, or three diffusion mechanisms. , Also, the activation and pyrolysis of biomasses have been understood to cause the formation of irregular carbon layers that comprised abundant small-sized pores, which played a vital role in the adsorption of target contaminants. ,, Noteworthy of mention is that numerous published papers focused and dwelt on adsorbents with a large surface area and pore size as the only platform in which more functional moieties (active sites) and pore channels could be made available for enhanced adsorption processes. Generally, it is understood that the small surface area and pore size of adsorbents prevent target contaminant molecules from accessing more active sites and pore channels during adsorption processes.…”
Section: Resultsmentioning
confidence: 99%
“…Drop wise 0.1 M NaOH or 0.1 M HCl was added until the desired value was obtained. The effect of parameters was determined by using a range such as pH (2)(3)(4)(5)(6)(7)(8), adsorbent dose (0.25-1.00 g), initial Pb(II) ion concentration (20-100 mg/L), contact time (0-120 min) and shaking speed 180 rpm at a room temperature of 28 °C. To optimize the conditions one parameter was kept different while other parameters were kept constant.…”
Section: Biosorption Experiments In Batch Methodsmentioning
confidence: 99%
“…( ) 1 e t e k log q -q = log q -t 2.303 (7) where, qe (mg/g) and qt (mg/g) are adsorption amount at equilibrium and reaction time t (min), respectively. k1 (min 1 ) is the rate constant in the pseudo-first-order adsorption process.…”
Section: Pseudo-first Order Reaction Modelmentioning
confidence: 99%
See 1 more Smart Citation